QUASARS – POINTERS TO AN INFINITE, ETERNAL AND DIALECTICAL UNIVERSE AND A REPUDIATION OF THE BIG BANG COSMOLOGY - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2023)
Quasars (quasi-stellar [star-like] radio sources) represent the critical criteria for choice between two opposite and widely different ontological and epistemological narrative of the universe. The first one, which is mainly based on mathematical idealism views the universe as deterministic and an essentially unidirectional condensation of diffuse matter created through a single primordial explosion (The Big Bang) about 13.8 billion years ago. The second view, based on (limited) observational and empirical evidence asserts a rather intrinsic and dialectical evolution (appearance/disappearance) of matter and motion in an infinite, eternal and ever-changing universe; where new cosmic bodies are formed from ejected and/or dissipated matter; from the core of the existing cosmic bodies.; mediated by chance and necessity.